Rain gods [compact disc, unabridged] - Burke, James Lee, 1936- (Simon & Schuster Audio, 2009)
Eager to escape his problematic past, Hackberry Holland acquires the sheriff's position in a rundown Texas border town. When authorities discover nine dead prostitutes buried in the desert, Hack must work with both Texas and Mexico, as well as face down hired gunmen, crooked strip club owners, and dubious drug lords, to solve the case.